2016
DOI: 10.1371/journal.pone.0156956
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study between Single Nucleotide Polymorphisms and Flight Speed in Nellore Cattle

Abstract: IntroductionCattle temperament is an important factor that affects the profitability of beef cattle enterprises, due to its relationship with productivity traits, animal welfare and labor safety. Temperament is a complex phenotype often assessed by measuring a series of behavioral traits, which result from the effects of multiple environmental and genetic factors, and their interactions. The aims of this study were to perform a genome-wide association study and detect genomic regions, potential candidate genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 145 publications
1
35
0
2
Order By: Relevance
“…This region and adjacent regions (regions 2.2-2.11) are located within QTL found in Limousin associated with carcass fat and carcass conformation (Purfield et al 2019). Furthermore, region 2.16 (ZHp = À3.17) contains NCKAP5, a gene associated in Nellore with flight speed, a temperament trait (Valente et al 2016). This gene has been associated with human attention deficit hyperactivity disorders (Lasky-Su et al 2008), schizophrenia and bipolar disorders (Wang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This region and adjacent regions (regions 2.2-2.11) are located within QTL found in Limousin associated with carcass fat and carcass conformation (Purfield et al 2019). Furthermore, region 2.16 (ZHp = À3.17) contains NCKAP5, a gene associated in Nellore with flight speed, a temperament trait (Valente et al 2016). This gene has been associated with human attention deficit hyperactivity disorders (Lasky-Su et al 2008), schizophrenia and bipolar disorders (Wang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Consecutive 20 SNPs, which explained 1% or more of the total genetic variance, based on the WssGWAS, were considered as a genomic window associated with the studied traits [ 37 , 38 , 39 ]. The Map Viewer tool for the bovine genome was used to identify positional candidate genes based on the starting and ending coordinates of each window using the UMD 3.1.1 assembly as the reference map ( ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the availability of genotype information on only a limited proportion of animals in some developing countries has promoted the implementation of the single-step methodology (ssGBLUP) (Misztal et al, 2009). In this model, pedigree and genomic relationships are combined into an H matrix to predict the genetic merit of the animal, which results in higher accuracy due to the utilization of all the available data (Misztal et al, 2009;Cardoso et al, 2015;Valente et al, 2016). Aguilar et al (2010) showed that a single-step methodology can be simple, fast, and accurate.…”
Section: Single-step Genomic Best Linear Unbiased Prediction (Ssgblup)mentioning
confidence: 99%